Les booktubers, nouveaux critiques ? - Sonia de Leusse (Strenae)
The development of YouTube channels, now an international phenomenon, seems to be broadening and reconfiguring the field of criticism: teenage and young adult readers address peers as they share their passion for reading by presenting the latest books they’ve read in the form of short videos. A channel’s audience and subscriber numbers can reach tens of thousands of internet users and followers—a size much more impressive than that of blogs and other pre-existing teenage critical book circles. Who are these amateur critics and dilettantes; what are their codes and main criteria in their presentations and discourse? Does BookTubing renew (or not) young adult book criticism?